Blue Economy Perspektif Maqashid Syariah - Ridho Erianto; Indra Mualim Hasibuan; Maryam Batubara (DPPM Universitas Pelita Bangsa, 2024)
Unethical use of marine resources is the cause of damage to marine ecosystems, this is not without reason, because there have been many cases of exploitation of marine resources revealed by the government, including exploitation of sea sand, illegal fishing, plastic waste and so on. This research is qualitative research using a literature study approach. The aim of the research is to describe the concept of blue economy from the perspective of maqashid sharia (daruriyah). The research results show that the blue economy principles consisting of: zero waste, natural efficiency and social care are in line with the five principles of maqashid sharia (daruriyah), namely hifdz al-din, hifdz al-nafs, hifdz al-aql, hifdz al-maal, and hifdz al-nasb. These five principles are the ultimate goal of the blue economy concept. Keywords: Blue Economy, Maqashid Syariah